20-Hydroxyeicosatetraenoic acid antagonist attenuates the development of malignant hypertension and reverses it once established: a study in Cyp1a1-Ren-2 transgenic rats. Issue 5 (12th September 2018) - Sedláková, Lenka; Kikerlová, Soňa; Husková, Zuzana; Červenková, Lenka; Chábová, Věra Čertíková; Zicha, Josef; Falck, John R.; Imig, John D.; Kompanowska-Jezierska, Elzbieta; Sadowski, Janusz; Krátký, Vojtěch; Červenka, Luděk; et al.
Abstract : We hypothesized that vascular actions of 20-hydroxyeicosatetraenoic acid (20-HETE), the product of cytochrome P450 (CYP450)-dependent ω-hydroxylase, potentiate prohypertensive actions of angiotensin II (ANG II) in Cyp1a1-Ren-2 transgenic rats, a model of ANG II-dependent malignant hypertension. Therefore, we evaluated the antihypertensive effectiveness of 20-HETE receptor antagonist (AAA) in this model. Malignant hypertension was induced in Cyp1a1-Ren-2 transgenic rats by activation of the renin gene using indole-3-carbinol (I3C), a natural xenobiotic. Treatment with AAA was started either simultaneously with induction of hypertension or 10 days later, during established hypertension. Systolic blood pressure (SBP) was monitored by radiotelemetry, indices of renal and cardiac injury, and kidney ANG II levels were determined. In I3C-induced hypertensive rats, early AAA treatment reduced SBP elevation (to 161 ± 3 compared with 199 ± 3 mmHg in untreated I3C-induced rats), reduced albuminuria, glomerulosclerosis index, and cardiac hypertrophy ( P <0.05 in all cases). Untreated I3C-induced rats showed augmented kidney ANG II (405 ± 14 compared with 52 ± 3 fmol/g in non-induced rats, P <0.05) which was markedly lowered by AAA treatment (72 ± 6 fmol/g). Remarkably, in TGR with established hypertension, AAA also decreased SBP (from 187 ± 4 to 158 ± 4 mmHg, P <0.05) and exhibited organoprotective effects in addition to marked suppression of kidney ANG II levels. In conclusion, 20-HETE antagonist attenuated the development and largely reversed the established ANG II-dependent malignant hypertension, likely via suppression of intrarenal ANG II levels. This suggests that intrarenal ANG II activation by 20-HETE is important in the pathophysiology of this hypertension form.